A dimensional metrology-based approach for corrosion measurement of ship grade steels exposed to various marine environmental conditions - Abbas, Muntazir; Simms, Nigel J.; Lao, Liyun; Malik, Owais A.; Syed, Adnan U.; Sarfraz, Syed Ali; Ashraf, Luqman; Rizvibar, Syed Haider M. (SAGE, 2021)
Corrosion-induced degradation in marine steel structures is highly dependent on the surrounding environmental conditions and sea water compositions that varies significantly around global sea water bodies. This research investigates the corrosion behaviour of ship-grade steels exposed under different sea water compositions and environmental conditions typical of the Arabian Sea. More, environmental conditions spanning those anticipated for the shipping structures operating in the highly saline and warmest regions in the Arabian Sea have been simulated in laboratory-based experiments by using heated and aerated artificial sea water. Following their exposures, the corrosion performance of coupons has been investigated using the standard weight loss and a new dimensional metrology-based approach. Besides, the corrosion products formed on the steel surfaces have been characterised using various analytical techniques. Considerably higher corrosion losses and maximum corrosion depths were observed in the nutrient-rich polluted sea waters than those recorded in the natural sea waters, as well as in the simulated artificial sea water conditions.
Keywords: pollutant-rich sea water; natural sea water; dissolved inorganic nitrogen; Arabian Sea; Marine corrosion